Marketing / Concepts and Strategies - Ferrell O.C; Pride William M (Houghton Mifflin Company, 1993)
An Analysis of Marketing Opportunities, Product Decisions, Distribution Decisions, Promotion Decisions, Pricing Decisions, Marketing Management, Selected Applications.
An Analysis of Marketing Opportunities, Product Decisions, Distribution Decisions, Promotion Decisions, Pricing Decisions, Marketing Management, Selected Applications.